Starting over on Blackberry Lane - Roberts, Sheila, 1951- (Roberts, Sheila, 1951- Life in Icicle Falls., 2017)
Stefanie Stahl has a husband with renovation ADD. He can<U+2019>t seem to finish anything he starts, and her house is littered with his “projects.” If he doesn<U+2019>t smarten up, she swears she<U+2019>s going to murder him and bury him under the pile of scrounged lumber in the backyard. Her friend Griffin James is suddenly single and thinking maybe she needs to sell her fixer-upper and follow her career bliss up the ladder of success, even if that scary ladder is clear across the country. But getting her place ready to sell proves harder than she originally thought. She needs help. She<U+2019>s not the only one. Cass Wilkes, their neighbor, has an empty nest<U+2014>with a leaking roof. When her ceiling crashes in, she knows it<U+2019>s time to do something. When Grant Masters offers his handyman services at a fund-raiser auction, the three women go in together to outbid the competition and win their man. (Cass<U+2019>s friends think she should win Grant in a different way, too!) Now it<U+2019>s time to make some improvements<U+2026>in their houses and their lives.